2010
DOI: 10.1002/jpln.200800225
|View full text |Cite
|
Sign up to set email alerts
|

Leaching of heavy metals and nutrients from calcareous sandy‐loam soil receiving municipal solid sewage sludge

Abstract: Leaching column experiments were conducted to determine the degree of mobility of heavy metals (HMs) and nutrients after the addition of municipal solid sewage sludge (MSS) in a sandy-loam soil. Treatments were (1) soil application of low metal content MSS, (2) soil application of metal-enriched municipal solid sewage sludge (EMSS), and (3) control. The MSS application represented a dose of 200 Mg dry weight (dw) ha -1 . Soil columns were incubated at room temperature for 15 d and were irrigated daily with dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…It became a common practice to add municipal sewage sludge (MSS) (Smith, 1996;Islas-Espinoza et al, 2014), biosolids (Shu et al, 2016) and manure to soils in many countries around the world to supply P, nitrogen and other macro-and micro-nutrients. In many parts of Iran MSS (Raiesi et al, 2015;Rezapour et al, 2012;Jalali and Arfania, 2010) and manures (Jalali and Ostovarzadeh, 2009) is used to supply plants with P and other nutrients. Raiesi et al (2015) indicated that application of MSS to the calcareous soils increased both organic and calcium phosphate fractions.…”
Section: Degree Of P Saturationmentioning
confidence: 99%
“…It became a common practice to add municipal sewage sludge (MSS) (Smith, 1996;Islas-Espinoza et al, 2014), biosolids (Shu et al, 2016) and manure to soils in many countries around the world to supply P, nitrogen and other macro-and micro-nutrients. In many parts of Iran MSS (Raiesi et al, 2015;Rezapour et al, 2012;Jalali and Arfania, 2010) and manures (Jalali and Ostovarzadeh, 2009) is used to supply plants with P and other nutrients. Raiesi et al (2015) indicated that application of MSS to the calcareous soils increased both organic and calcium phosphate fractions.…”
Section: Degree Of P Saturationmentioning
confidence: 99%
“…General concerns have been raised about increasing deterioration of natural waters by liquid MSS application, but little study has been conducted to investigate the fate of heavy metals and their speciation when incorporated with solid sewage sludge in calcareous soil. Previous soil leaching experiments showed that Ni and Pb losses in the percolate were low relative to total amounts of metal applied (Jalali and Arfania 2010). Thus, the aim of the present study was to investigate the distribution of Cd, Cu, Pb, Ni, and Zn in the soil column and change of heavy metals in different fractions in a calcareous sandy soil receiving MSS.…”
Section: Introductionmentioning
confidence: 98%
“…In comparison to clean groundwater-irrigated soil and soil without any compost, wastewater-irrigated soil and soil containing compost or sewage sludge have some advantages such as: (i) more organic carbon, (ii) more available nitrogen, phosphorus and potassium, (iii) more crop production, (iv) better soil physical, chemical and biological properties, (v) more available water content and (vi) less erosion (Siebe, 1998;Tejada et al, 2001;Zheljazkov and Warman, 2004;Wei and Liu, 2005;Tabari and Salehi, 2009;Baldantoni et al, 2010;Jalali and Arfania, 2010;Mojiri, 2010;Singh and Agrawal, 2012).…”
Section: Introductionmentioning
confidence: 98%
“…However, phosphorus leaching can occur in sandy soils (Guertal et al, 1991) and other types of soils with high P, due to continuous P application (Heckrath et al, 1995). Jalali and Arfania (2010) investigated the effect of sewage sludge on leaching nutrients from a calcareous sandy-loam soil. They found that the amounts of P (2.97 kg ha −1 ) leached from column which received sewage sludge was significantly larger than that from control treatment (1.54 kg ha −1 ).…”
Section: Introductionmentioning
confidence: 99%